PENGARUH DOSIS PUPUK N TERHADAP VARIETAS KENAF KR-11 (Hibiscus cannabinus L.) PADA TANAH LATOSOL Influence of Fertilizer Dosage on kenaf KR-11 variety (Hibiscus cannabinus L) on Latosol Soil - Haryatie Sarie; Daryono (Politeknik Pertanian Negeri Samarinda, 2017)
One step that can be taken for soil fertility is the addition and use of an organic fertilizer. Plants require fertilizer tomeet the nutritional needs during the plant growth process. One type of an organic fertilizer is N fertilizer(nitrogen). N fertilizer is one way to increase the growth and yield of kenaf plant fiber. This study uses the basicdesign used is Randomized Block Design (RAK) with three factorials. Dose of urea fertilizer (N) n1: 30g urea /plot, n2: 40g urea / plot, n3: 50g urea / plot and Varieties kenaf (V) v1: KR-11, The data of the research wereanalyzed by variance if the difference was significant in the treatment, then continued with BNT test (Beda NyataKecil Kecil) 5% to compare the average of treatment. From result of research of BNT test of 5% level, average ofplant height of kenaf KR-11 age 60 HST showed that interaction of single factor of nitrogen fertilizer (N)significantly different to plant height 60 HST ie treatment n2 = 174,33cm, n3 = 172.54 cm and the lowest intreatment n1 = 169,86 cm. Meanwhile, based on BNT test of 5% level, the average weight of dried fiber kenaf KR11highest shown by nitrogen fertilizer n2 is 32,95 g and n3 32.19 g. While the lowest average yield shown by n1 nitrogen fertilizer that is 31.29 g